2013
DOI: 10.1089/ten.tea.2012.0665
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Glue Improves the Therapeutic Effect of MSCs by Sustaining Survival and Paracrine Function

Abstract: Fibrin glue has been widely investigated as a cell delivery vehicle for improving the therapeutic effects of mesenchymal stem cells (MSCs). Implanted MSCs produce their therapeutic effects by secreting paracrine factors and by replacing damaged tissues after differentiation. While the influence of fibrin glue on the differentiation potential of MSCs has been well documented, its effect on paracrine function of MSCs is largely unknown. Herein we investigated the influence of fibrin glue on the paracrine effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 41 publications
2
38
0
3
Order By: Relevance
“…The ASCs injected with fibrin glue may have a long‐term synergistic effect with cells injected under the subepithelial layer of the fistula tract. ASCs in fibrin glue matrix effectively release growth factors to enhance wound healing and soluble factors to inhibit immune response by suppressing both T‐cell proliferation and secretion of proinflammatory cytokines from the activated T cells, although cells in fibrin glue matrix may not migrate to the tissue [29]. In addition, the ASCs used in our clinical trial may have different characteristics than those of other clinical trials, even if MSCs were harvested from the same adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The ASCs injected with fibrin glue may have a long‐term synergistic effect with cells injected under the subepithelial layer of the fistula tract. ASCs in fibrin glue matrix effectively release growth factors to enhance wound healing and soluble factors to inhibit immune response by suppressing both T‐cell proliferation and secretion of proinflammatory cytokines from the activated T cells, although cells in fibrin glue matrix may not migrate to the tissue [29]. In addition, the ASCs used in our clinical trial may have different characteristics than those of other clinical trials, even if MSCs were harvested from the same adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…They may also provide paracrine effects for vascularization and muscle regeneration. MSCs are known to secrete angiogenic growth factors like VEGF, bFGF and PDGF for vascularization, and IGF-1 for promyogenesis [76, 77]. However, since the cell survival in this group is low (Figure 5), the improvement on blood perfusion recovery and muscle regeneration was limited.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix stiffness can drive the stromal cell lineage and differentiation 32,33 . Kim et al similarly reported that mesenchymal stem cells maintained a rounded shape in fibrin gel with a higher, nonphysiological concentration of fibrinogen (127 to 256 mg/mL) 34 . In contrast, our physiological controls, as well as our low-low and low-high groups, showed a spindle-shape cell morphology, which reflects the morphology of tenocytes 35,36 .…”
Section: Effect O F Fibrin F O R M U L At I O N O N T E N D O N R E Pmentioning
confidence: 96%